Angel investing: Changing strategies during volatile times - Jeffrey E. Sohl (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
Changing conditions in the angel market offer a unique opportunity to further knowledge and understanding about angel investing in the US during times of economic volatility. To identify trends in the angel market, this research examines changes in characteristics and investment behavior during a time of market expansion and contraction (2000 to 2001). While business angels remain the leading source of seed capital for business ventures, depressed yield rates and increased due diligence indicate that investors are retreating to more fundamental approaches.
Keywords: 650